Trajetória da riqueza, composição em espécies e grupos funcionais de aves ao longo de 14 anos numa extensa área restaurada - Oliveira, Yasmin Carolina Lopes de (Universidade Federal de São Carlos, 2024)
Riparian environments have high habitat heterogeneity and species diversity, contributing significantly to regional biodiversity. The composition and structure of bird communities can respond rapidly to changes in forest structure throughout succession, and can thus be a good indicator of ecosystem restoration. Thus, the objective of this study was to evaluate changes in the terrestrial bird community that occurred annually over a 14-year period since the first inventory conducted in 2009, and to evaluate the effect of forest restoration actions on the richness, species composition and characteristics of avifauna in a restored area on the banks of the Anhanguera Small Hydroelectric Plant (SHP) reservoir. The Anhanguera Small Hydroelectric Plant (SHP) is located on the Sapucaí Mirim River, in the northeastern region of the state of São Paulo. The terrestrial avifauna survey was carried out in the riparian forests surrounding the Anhanguera Small Hydroelectric Plant (SHP) reservoir, taking into account the remaining forest fragments and in the forest restoration areas comprising a total area of ​​approximately 70 ha. Terrestrial bird species were characterized according to their diet, forest dependence and foraging stratum. Our results showed that forest restoration actions resulted in a significant increase in bird species richness and similarity in species composition after 14 years. The increase in bird richness was strongly dependent on the increase in biomass of individual tree species over time. The proportion of species with high and medium forest dependence and the proportion of birds foraging in tree canopies increased strongly in the restored area over time. We also detected a significant increase in frugivorous birds and the emergence of nectarivores, suggesting that restoration after 14 years follows a trajectory towards reference forests. Our results showed that bird species composition varied greatly throughout the development of the forest, from the restoration action towards the reference areas. Identifying changes in species composition and functional groups of birds can help guide forest recovery and conservation actions for tropical birds.
Trajectory of bird richness, species composition and functional groups over 14 years in a large restored area
Keywords: Diversidade de aves; Restauração florestal; Frugívoros; Nectarívoros; Central hidrelétrica; CIENCIAS BIOLOGICAS::ECOLOGIA; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA APLICADA